Analysis of hospitalization for respiratory diseases in the state of Sergipe between 2010 and 2020 (Research, Society and Development, 2022)
Respiratory problems are a public health problem and an important cause of morbidity and mortality in Brazil and worldwide. Therefore, this work aims to carry out an epidemiological survey of respiratory disorders as the main cause of hospital admissions in reference services for the SUS in the state of Sergipe, between 2010 and 2020, in order to facilitate planning and implementation of measures that can prevent these injuries. Data were collected through the Ministry of Health (DATASUS) and IBGE databases and were compiled into spreadsheets in the Microsoft Office Excel program. Data analysis was performed by calculating relative frequencies, absolute frequencies, means and standard deviation of the variables studied. The data obtained showed a total of 75,058 hospitalizations for respiratory problems in the period studied in Sergipe, with an annual average of deaths of 11.3%. The underlying diseases that led to most hospitalizations were pneumonia and asthma. In addition, these hospitalizations were more prevalent in the groups of males, children between 0 and 4 years of age, people of mixed race and people residing in the Aracaju health region. After analyzing this study, it is noted that Sergipe, despite having lower rates of hospital admissions and deaths from respiratory diseases, compared to other states of the Federation, is in line with the prevalence presented in the literature for gender, ethnicity and main diagnosis as the cause of hospitalization.